-33-6y+19=-23y+56+7y

Simple and best practice solution for -33-6y+19=-23y+56+7y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -33-6y+19=-23y+56+7y equation:


Simplifying
-33 + -6y + 19 = -23y + 56 + 7y

Reorder the terms:
-33 + 19 + -6y = -23y + 56 + 7y

Combine like terms: -33 + 19 = -14
-14 + -6y = -23y + 56 + 7y

Reorder the terms:
-14 + -6y = 56 + -23y + 7y

Combine like terms: -23y + 7y = -16y
-14 + -6y = 56 + -16y

Solving
-14 + -6y = 56 + -16y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '16y' to each side of the equation.
-14 + -6y + 16y = 56 + -16y + 16y

Combine like terms: -6y + 16y = 10y
-14 + 10y = 56 + -16y + 16y

Combine like terms: -16y + 16y = 0
-14 + 10y = 56 + 0
-14 + 10y = 56

Add '14' to each side of the equation.
-14 + 14 + 10y = 56 + 14

Combine like terms: -14 + 14 = 0
0 + 10y = 56 + 14
10y = 56 + 14

Combine like terms: 56 + 14 = 70
10y = 70

Divide each side by '10'.
y = 7

Simplifying
y = 7

See similar equations:

| 7(x+2)=5x+2+6x | | 3x^3-10x^2+50x= | | -2a-9= | | 8(r-2)=r-22+5r | | x*x+x-1=0 | | 9x-4x+3=60 | | x^2+26x+64=0 | | K-14+5k=2(k+3) | | 6y=5x^2-2 | | x-2=x*x-1 | | K-18+5k=2(k+1) | | 2(9x-6)+8(6x-7)=-29 | | 19+6y-1=17y-9-2y | | -32-19y+19=-29y+31+6y | | 11k+2=k+18 | | (4x-3)(x+7)=(1-2x)(x-9) | | x^2-32x+256-37=0 | | -31-3y+18=-22y+3+15y | | -3c+5+5c=-3c+20 | | (2x+1)(x-16)=(3x-2)(x-6) | | 2t-1=3(t+3) | | Y=2x(7x-3) | | 9(3+2x)=10x+45 | | 8(y-2)=4y-28 | | 2-6x+10x=-2(-3x+4) | | 25+3y-6=13y-11-4y | | x^2-32x+256=37 | | 21+3y-2=13y-11-4y | | 2*3*2*11+9/3= | | 16-4x=3x+2 | | 7y-7=4y+2 | | (x-16)(x-16)= |

Equations solver categories